Kuwait : Staff Report for 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Kuwait's 2005 Article IV Consultation reports that the economic and financial positions are projected to remain strong mainly on the expectation that world oil prices will decline only gradually. Reflecting sharply higher oil prices and production, economic conditions improved significantly in 2003 and 2004. The main economic challenge facing Kuwait is to create sufficient employment opportunities for the rapidly growing national labor force by accelerating the growth of the private non-oil economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet